USING IMAGE MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES IN SCIENCE LEARNING FOR CLASS VI ELEMENTERY SCHOOL STUDENTS - Ainal Mardhiah Ainal mardhiah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The purpose of writing this article is to determine the use of image media to improve student learning outcomes in science learning in grade VI elementary school students. This study uses a type of classroom action research (CAR) where researchers and students are directly involved during the teaching and learning process. This research was conducted as a process of studying learning problems in the classroom that were not specifically arranged for research purposes, but CAR took place in real situations and conditions without being engineered. Therefore, the fairness of the class in the research process is a characteristic of classroom action research. This research cycle consists of 4 cycles, namely planning, action, observation, and reflection. The results of this study show that teacher activity in using image media in science learning in cycle I obtained a score of 75% (Good), in cycle II obtained a score of 92.85% (Very Good). Based on the data above, it can be seen that teacher activity in implementing learning using image media in science learning has increased so that it reaches the maximum limit. Student activity in learning using image media in science learning in cycle I obtained a score of 60% (Good), in cycle II obtained a score of 93.33% (Very Good). Based on the data above, it can be seen that student activities in implementing learning using picture media in science learning can achieve perfection with the achievement of a very good predicate. Based on the results of the final test conducted, the learning outcomes of grade VI students have increased. In cycle I, student learning outcomes only reached 60%, this has not achieved classical student learning completion. Students who achieved completion were 12 people and 16 people did not complete. In cycle II, student learning outcomes increased to 85.70% in this cycle, student learning outcomes reached the maximum limit and had achieved classical completion.